EXCLUSIVE RHO(0) PRODUCTION IN DEEP-INELASTIC ELECTRON-PROTON SCATTERING AT HERA - Derrick, M; Krakauer, D; Magill, S; Mikunas, D; Musgrave, B; Repond, J; Stanek, R; Talaga, R; Zhang, H; Ayad, R; Bari, G; Basile, M; et al. (1995)
The exclusive production of ρ0 mesons in deep inelastic electron-proton scattering has been studied using the ZEUS detector. Cross sections have been measured in the range 7 < Q2 < 25 GeV2 for γ*p centre of mass (c.m.) energies from 40 to 130 GeV. The γ*p → ρ0p cross section exhibits a Q-(4.2±0.8-0.5+1.4) dependence and both longitudinally and transversely polarised ρ0's are observed. The γ*p → ρ0p cross section rises strongly with increasing c.m. energy, when compared with NMC data at lower energy, which cannot be explained by production through soft pomeron exchange. The data are compared with perturbative QCD calculations where the rise in the cross section reflects the increase in the gluon density at low x.